The Management of Bone Defects in Periarticular Knee Injuries: A Review Article - Buck, Brian; Murtha, Yvonne M. (The Journal of Knee Surgery, 2017)
Traumatic bone defects of the distal femur and proximal tibia present treatment challenges for the orthopaedic traumatologist. In addition to bone loss, significant soft tissue compromise and cartilage defects leave the patient and surgeon with few reconstructive options for proper long-term joint function. These injuries are often complicated by delayed healing, nonunion, malunion, infection, and poor subjective patient outcomes. There are a variety of clinical problems associated with the treatment of periarticular fractures about the knee. This article will describe the surgical options for these difficult problems.
Keywords: bone defect; periarticular fracture; knee; fracture